Postkeynesianski pogled na mala in srednja podjetja - Lah, Marko (Teorija in praksa, 2019)
The post-Keynesian theory of the firm concentrates on large corporations and ignores small and medium-sized enterprises (SMEs). The paper therefore analyses the relationship between big corporations and SMEs using the concepts of power and transaction costs. We outline the possible types of this relationship and analyse the position of a subcontractor, especially its inability to grow due to mark-down pricing. We conclude that Williamson's theory of transaction costs and the related concept of asset specificity help understand the power relations seen in corporate networks. This proves the possibility of bringing together two paradigmatically different economic schools: Post-Keynesian Economics and Transaction Cost Economics.
Keywords: costs; majhna podjetja; medium-sized enterprises; post-keynesianism; small enterprises; srednja podjetja; stroški